s PENGARUH PEMBERIAN JUS BUAH NAGA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIADENGAN HIPERTENSI : PENGARUH PEMBERIAN JUS BUAH NAGA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIADENGAN HIPERTENSI - Rofia, Sofiatur; Wijaya, Arif; Roni, Faishol (WELL BEING, 2023)
ABSTRACT Background: Hypertension was a silent killer which the symptoms could be vary in each individual and were almost the same as the symptoms of other diseases and it caused the highest death in the world. One of the fruits that could be used to reduce hypertension was dragon fruit which was rich in potassium and flavonoids. Objective: to determine the effect of giving dragon fruit juice on blood pressure in the elderly with hypertension. Methodology: Search articles used Google Scholar, Science Direct, Pro Quest and Semantic Scholar to find articles according to inclusion and exclusion criteria, then reviewed. Results: Ten research journals showed that the average systolic and diastolic blood pressure decreased after being given dragon fruit juice by giving 100 grams of dragon fruit juiced using 150 ml of water and consumed 2 times a day with varying lengths of administration between 3-7 days. It decreased systolic blood pressure between 6.98-29.93 mmHg. The p-value results from 10 research journals showed that the pvalue was < (0.05). Keywords: dragon fruit, blood pressure, hypertension, Literature review.